1975
DOI: 10.1073/pnas.72.10.3975
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of mouse interferon by translation of its messenger RNA in a cell-free system.

Abstract: A fraction of mouse RNA containing messenger RNA coding for mouse interferon was translated with high efficiency in a wheat germ system into a fully active product. This product fulfills the criteria for mouse interferon, namely: (1) it was active against vesicular stomatitis virus and herpes simplex virus in mouse cells; (2) its antiviral activity was species specific; (3) its activity was completely neutralized by mouse anti-interferon serum. The synthesis of interferon in this cell-free system requires the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…premature to conclude that the poly(A)-lacking fraction does not contain any interferon mRNA (24)(25)(26). DISCUSSION In previous reports, we have systematically evaluated several different hypotheses that might explain superinduction of human interferon production (for reviews see refs.…”
Section: Synthesis and Inactivation Of Interferon Mrna In Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…premature to conclude that the poly(A)-lacking fraction does not contain any interferon mRNA (24)(25)(26). DISCUSSION In previous reports, we have systematically evaluated several different hypotheses that might explain superinduction of human interferon production (for reviews see refs.…”
Section: Synthesis and Inactivation Of Interferon Mrna In Humanmentioning
confidence: 99%
“…It has been discovered recently that polyadenylylated RNA extracted from interferon-producing human or mouse cells can be translated in wheat-germ, mouse Ehrlich ascites, Krebs-II ascites, and rabbit reticulocyte cell-free translation systems and in the Xenopus laets* oocyte, with the production of biologically active and specific interferon (24)(25)(26).…”
mentioning
confidence: 99%
“…The oocyte product resulting from injection of Namalva mRNA exhibited a similar molecular weight distribution with the peak of activity corresponding to 16,000 daltons. DISCUSSION Recent studies have shown that mRNA extracted from cells actively producing interferon can direct interferon synthesis in some heterologous intact animal cells (32)(33)(34) or in cell-free systems (18,35,36). In this study, we used X. Iaevis oocytes for the translation of human interferon mRNA isolated from two different cellular sources.…”
Section: Synthesis Of Human Interferon By X Laevis Oocytesmentioning
confidence: 99%
“…This scheme was originally based on results obtained with a limited number of metabolic inhibitors, notably actinomycin D and cycloheximide, although recently much more direct evidence has been obtained for the production of a new interferon messenger RNA after treatment of cells with an interferon inducer (De Maeyer-Guignard et al 197z;Kronenberg & Friedman, 1975;Pestka et al 1975;Reynolds et al 1975;Thang et al 1975). A second gene system, which represses the interferon gene, has also been invoked from the results of experiments in which actinomycin D and cycloheximide were added after interferon production had started.…”
Section: Introductionmentioning
confidence: 99%